How IPO firms' product innovation strategy affects the likelihood of post-IPO acquisitions? - Kooli, Maher; Zhang, Aoran; Zhao, Yunfei (Journal of Corporate Finance, 2022)
This study investigates why newly listed firms become M&A targets shortly after their initial public offering (IPOs) from the perspective of product innovation. We find strong empirical evidence that IPOs with less established trademarks increase the likelihood of becoming IPO targets. We also find that the negative relation between established trademarks and the likelihood of becoming IPO targets is more pronounced in highly competitive industries and is primarily driven by the M&A supply side. IPOs with more established trademarks can fend themselves against the product market race as independent firms. They can meanwhile realize superior post-IPO financial as well as innovation performance. To acquire such firms, acquirers need to offer substantially higher takeover premiums. However, some empirical evidence suggests that less product innovation-intensive IPOs tend to deliberately seek potential acquirers to support their product market competing position and therefore are more likely to initiate an M&A deal shortly after going public.